2019
DOI: 10.1016/j.redox.2018.101092
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of decaffeinated coffee protects against the development of early non-alcoholic steatohepatitis: Role of intestinal barrier function

Abstract: BackgroundNon-alcoholic fatty liver disease (NAFLD) is one of the most common liver diseases worldwide lacking universally accepted therapies. Studies suggest that coffee consumption is associated with a reduced risk of NAFLD; however, molecular mechanisms and ingredients involved remain to be fully understood. Here, we determined the effects of regular intake of decaffeinated coffee on the development of NAFLD in mice, and molecular mechanisms involved.MethodsFemale C57BL/6J mice (n = 6–7/ group) were pair-fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 71 publications
1
17
0
Order By: Relevance
“…An improved gut barrier function induced by coffee in the present study could explain the reduced liver steatosis and the lower serum levels of cholesterol and glucose. Moreover, it is in agreement with our previous observation in rats ( 41 ) and with the recent findings of Brandt et al ( 17 ) who found that consumption of decaffeinated coffee in mice fed with a high-fat, -fructose and -cholesterol diet increased intestinal protein expression of zonulin-1 and occludin, reduced bacterial endotoxin concentration in portal blood and mRNA expression of lipopolysaccharide-binding protein in the liver compared with the mice fed with the same diet without coffee. It is well known that HFD is associated with dysbiosis, intestinal mucosa inflammation and a leaky gut condition leading to metabolic endotoxaemia and consequent liver fat accumulation and inflammation ( 42 ) .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…An improved gut barrier function induced by coffee in the present study could explain the reduced liver steatosis and the lower serum levels of cholesterol and glucose. Moreover, it is in agreement with our previous observation in rats ( 41 ) and with the recent findings of Brandt et al ( 17 ) who found that consumption of decaffeinated coffee in mice fed with a high-fat, -fructose and -cholesterol diet increased intestinal protein expression of zonulin-1 and occludin, reduced bacterial endotoxin concentration in portal blood and mRNA expression of lipopolysaccharide-binding protein in the liver compared with the mice fed with the same diet without coffee. It is well known that HFD is associated with dysbiosis, intestinal mucosa inflammation and a leaky gut condition leading to metabolic endotoxaemia and consequent liver fat accumulation and inflammation ( 42 ) .…”
Section: Discussionsupporting
confidence: 94%
“…The scientific literature indicates that gut health is implicated in the development and progression of liver diseases and very little recent evidence exists that coffee can modulate some intestinal functions ( 17 ) .…”
mentioning
confidence: 99%
“…Previous studies of our group have shown that within 6-8 weeks of feeding a BFC, mice develop severe steatosis with early signs of inflammation, which progresses to early steatohepatitis after 13 weeks of feeding [37,38]. In line with our earlier studies, in livers of BFC-fed mice macrovesicular steatosis and inflammatory foci were present (see Fig 2 and Table 3) and NAS as well as hepatic triglyceride levels were significantly higher than those in both control groups (p<0.05 in comparison to both, C-and CO-fed animals and parameters, see Fig 2 and Table 3).…”
Section: Effect Of Extra Virgin Olive Oil On Markers Of Liver Damagementioning
confidence: 80%
“…The results of this study cannot attribute the inhibitory effects of coffee on NAFLD/NASH to caffeine or CGA, and other ingredients of coffee might exert inhibitory effects. It was recently reported that consumption of decaffeinated coffee protected against the development of early NASH in mice [ 38 ].…”
Section: Discussionmentioning
confidence: 99%